Modelling heat transfer in an intumescent paint and its effect on fire resistance of on-board hydrogen storage. (16th March 2017) - Kim, Y.; Makarov, D.; Kashkarov, S.; Joseph, P.; Molkov, V.
Abstract: This paper describes a 1-D numerical model for the prediction of heat and mass transfer through an intumescent paint that is applied to an on-board high-pressure GH2 storage tank. The intumescent paint is treated as a composite system, consisting of three general components, decomposing in accordance with independent finite reaction rates. A moving mesh, that is employed for a better prediction of the expansion process of the intumescent paint, is based on the local changes of heat and mass. The numerical model is validated against experiments by Cagliostro et al. (1975). The overall model results are used to estimate effect of intumescent paint on fire resistance of carbon-fibre reinforced GH2 storage.